Investigation on the Impact of Biofield Energy Treatment on the Physical, Thermal and Spectroscopic Characteristics of Zinc Chloride - Kumar Trivedi, Mahendra; Jana, Synthesis (Journal of Advanced Pharmaceutical Science And Technology, 2021)
Zinc is an essential trace mineral that plays an important role in the human body as a regulator for different enzymatic systems. It is used in various supplements in the form of zinc chloride to meet the daily requirements. This study was designed with the aim to investigate the impact of The Trivedi Effect®- Energy of Consciousness Healing Treatment on the various physical, thermal, and spectral properties of zinc chloride. The study involves dividing the zinc chloride sample in two parts, followed by keeping the first part untreated and named it the control sample. Besides, The Trivedi Effect®- Biofield Energy Healing Treatment was provided to the other part remotely by the renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi and the sample was termed as Biofield Energy Treated sample. Later on, both the samples were analyzed using PXRD, PSA, DSC, UV-Vis, and FT-IR analytical techniques. The PXRD analysis revealed the significant changes in the crystallite sizes (from -66.68% to 25.02%) and the relative peak intensities (from -81.35% to 141.22%) along with 26.46% decrease in the average crystallite size of the Biofield Energy Treated sample, compared with the control sample. Additionally, the treated sample showed reduction in the particle sizes d10, d50, d90, and D(4,3) values by 92.18%, 23.24%, 14.48%, and 29.31%, respectively as compared to the control sample. However, the surface area of the treated sample was observed to be significantly increased by 224.57%, compared to the control sample. The DSC analysis revealed slight increase in the melting and decomposition temperature of the Biofield Energy Treated sample by 0.84% and 3.62%, respectively; along with the significant increase in the latent heat of melting and decomposition by 24.85% and 123.23%, respectively, compared to the control sample. It showed that the thermal stability of the treated sample was significantly increased. However, the UV-Vis and FT-IR studies revealed that the structural properties of the control and treated samples were remained same. The overall study represents that The Trivedi Effect®- Energy of Consciousness Healing Treatment may be used to generate a polymorphic form of zinc chloride, which might possess enhanced solubility, dissolution and bioavailability profile along with improved thermal stability, compared to the control sample. Such properties of the treated zinc chloride may ensure its efficacy, stability and safety during the process of shipment, handling, and storage; thus, The Trivedi Effect®-Energy of Consciousness Healing Treated zinc chloride would be useful for designing the better formulation with enhanced bioavailability, stability and efficacy profile.
Keywords: Zinc Chloride; Powder X-Ray Diffraction (PXRD); Differential Scanning Calorimetry (DSC); Fourier-Transform Infrared Spectroscopy (FT-IR); Particle Size